2007
DOI: 10.4049/jimmunol.179.10.6494
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD8+ T Cells Require CD28 Costimulation

Abstract: CD8+ T cells are a critical component of the adaptive immune response against infections and tumors. A current paradigm in immunology is that naive CD8+ T cells require CD28 costimulation, whereas memory CD8+ T cells do not. We show here, however, that during viral infections of mice, costimulation is required in vivo for the reactivation of memory CD8+ T cells. In the absence of CD28 costimulation, secondary CD8+ T cell responses are greatly reduced and this impairs viral clearance. The failure of CD8+ T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 74 publications
8
151
0
Order By: Relevance
“…This suggests that the virus-specific CD8 + T cells during the effector phase need both IL-15 and costimulation signals as prosurvival factors. Our current study reveals an unappreciated role of CD28 costimulation during the CD8 + T cell effector phase and may explain the need for CD28 costimulation recently described by us and others for the generation of optimal secondary responses from memory CD4 + and CD8 + T cells (25,47,48). In addition to this, we show that the absence of CD28 costimulation and antigenic signals at the effector phase has an impact on viral clearance, as our studies show that there is decreased viral clearance in the absence of DCs at the effector stage most likely due to the reduced numbers of virus-specific CD8 + T cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This suggests that the virus-specific CD8 + T cells during the effector phase need both IL-15 and costimulation signals as prosurvival factors. Our current study reveals an unappreciated role of CD28 costimulation during the CD8 + T cell effector phase and may explain the need for CD28 costimulation recently described by us and others for the generation of optimal secondary responses from memory CD4 + and CD8 + T cells (25,47,48). In addition to this, we show that the absence of CD28 costimulation and antigenic signals at the effector phase has an impact on viral clearance, as our studies show that there is decreased viral clearance in the absence of DCs at the effector stage most likely due to the reduced numbers of virus-specific CD8 + T cells.…”
Section: Discussionsupporting
confidence: 60%
“…RNA was isolated by the Qiagen RNeasy kit (Qiagen). The isolated RNA was then used for cDNA synthesis, and virus was measured by real-time PCR as previously described (25). Viral loads of the experimental samples were calculated using a standard curve of a stock PR8 virus with known concentration of virus 50% tissue culture-infective dose per milliliter.…”
Section: Determination Of Viral Loadmentioning
confidence: 99%
“…Our finding that memory T-cell reactivation by either anti-CD40 or sCD70 is dependent on CD80/86 confirms previous studies showing that CD28/80/86 are necessary for memory CD8 + T-cell responses after infection with vaccinia, influenza, or lymphocytic choriomeningitis virus (LCMV) and for memory CD4 + T-cell expansion and IL-2 secretion after rechallenge with antigenic protein [24][25][26][27]. However, whether CD27 similarly plays a role during memory T-cell activation has been less clear; many studies that sought to address this question have made use of CD27-deficient or CD70-overexpressing mice in which interpretation of the memory CD8 + T-cell response is complicated by the impact of CD27/CD70 signals on CD8 + T-cell priming/imprinting and memory differentiation [6,9,12,41,42].…”
Section: Discussionsupporting
confidence: 90%
“…While some studies suggest that memory T cells do not require costimulation for reactivation, others have reported that costimulation remains necessary for their recall activation and expansion in vivo (40)(41)(42)(43)(44)(45). By carefully tracking endogenous donor-specific T cells using the IFN-γ ELISPOT assay as well as with fluorescently labeled 2W:I-A b and OVA:K b multimers, we observed that CTLA4-Ig was able to prevent the expansion of donor-specific T cells in sensitized mice.…”
Section: Cd4mentioning
confidence: 99%